The treatment of metastatic renal cell carcinoma - Ivanyi, Philipp; Fröhlich, Tabea; Grünwald, Viktor; Zschäbitz, Stefanie; Bedke, Jens; Doehn, Christian (Deutsches Ärzteblatt, 2024)
In 2020, 4830 women and 9330 men in Germany received a diagnosis of renal cell carcinoma (RCC. Their mean age on diagnosis was 68 in men and 71 in women. The main etiological risk factors are smoking, high blood pressure, and obesity (1)....
Gesehen am 30.07.2025